2 - The Role of NGOs in Fostering Development and Good Governance at the Local Level in Africa with a Focus on Kenya*: DOI: 10.4314/ad.v29i4.22205 - Oyugi, Walter O. (Africa Development, 2004)
Non-goveramental organisations have since the colonial period played a major role in socio-economic development in Africa. This role has increased in the post independence period, especially from the 1980s, following the demon strated failure of the state all over the continent, as a credible provider of basic needs services to the poor both in the rural and urban slums. As a result, instead of channelling development assistance through the state, some donor agencies have during the last two decades or so, opted to do so through non-state actors - especially the NGOs. The Kenyan experience demonstrates that the NGO sector has since the 1980s emerged as a major player in the design and imple mentation of projects as well as the actual provision of basic needs services to the disadvantaged groups both in the rural and urban areas. Although they are individually engaged in diverse activities, the Kenyan data suggests that the concentration of their activities is - in the social sector (education, health, gen eral welfare). The operational strategies employed to reach the intended benefi ciaries varies between direct and indirect interventions depending on the serv ice to be delivered and the institutional configuration on the ground. Where NGOs have opted for direct linkage with service recipients, their activities have tended to elicit negative response from the state as the latter usually prefers to act as intermediary between non-state actors and the service recipients. The impact of NGOs has varied both in terms of quality and quantity of service provided. The variation assumes both service and areal (i.e. spatial) dimensions, and the factors accounting for the variation are the sources as well as commitment by the founders of the organ sions and objectives. The Kenyan case study demonstrates emerged as a major player in the provision of basics needs services.